2015
DOI: 10.1111/imj.12736
|View full text |Cite
|
Sign up to set email alerts
|

Familial colorectal cancer

Abstract: Identifying individuals with a genetic predisposition to developing familial colorectal cancer (CRC) is crucial to the management of the affected individual and their family. In order to do so, the physician requires an understanding of the different gene mutations and clinical manifestations of familial CRC. This review summarises the genetics, clinical manifestations and management of the known familial CRC syndromes, specifically Lynch syndrome, familial adenomatous polyposis, MUTYH‐associated neoplasia, ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 87 publications
(114 reference statements)
0
8
0
Order By: Relevance
“…The inherited genetic risk of CRC can be partly accounted for by a combination of rare high-penetrance mutations and large numbers of common genetic variants each conferring small risk 6. Although a number of highly penetrant mutations (eg, DNA mismatch repair genes, APC , SMAD4 , LKB1/STK11 , MUTYH ) have been identified to influence CRC susceptibility with large effects, overall they account for only 2%–5% of incident CRC cases in the general population because these mutations are very rare 7–9. Candidate gene association studies have investigated the role of a large number of common genetic variants in CRC risk, but only a small number of them have been successfully replicated in subsequent studies 10 11…”
Section: Introductionmentioning
confidence: 99%
“…The inherited genetic risk of CRC can be partly accounted for by a combination of rare high-penetrance mutations and large numbers of common genetic variants each conferring small risk 6. Although a number of highly penetrant mutations (eg, DNA mismatch repair genes, APC , SMAD4 , LKB1/STK11 , MUTYH ) have been identified to influence CRC susceptibility with large effects, overall they account for only 2%–5% of incident CRC cases in the general population because these mutations are very rare 7–9. Candidate gene association studies have investigated the role of a large number of common genetic variants in CRC risk, but only a small number of them have been successfully replicated in subsequent studies 10 11…”
Section: Introductionmentioning
confidence: 99%
“…Hagiwara et al 16 showed that anthocyanin-enriched extracts from a purple sweet potato and red cabbage inhibited associated colorectal carcinogenesis in F344/DuCrj rats initiated with 2-dimethylhydrazine and received 2-amino-1-methyl-6-phenylimidazo[4,5-b] pyridine in the diet. 15 However, the present study is the first to demonstrate a chemopreventative effect of purple sweet potato in the APC MIN mouse, a model that may be more germane to human CRC, where the APC mutation is often inherited or occurs sporadically.…”
Section: Discussionmentioning
confidence: 71%
“…In principle, CRC can be prevented at the molecular level by impeding carcinogenesis through modification of behavior and diet or by using chemical agents. 15 Many presumed chemopreventive compounds have been recognized and generally categorized as ‘cancer-blocking’ or ‘cancer-suppressing’ agents according to the site along the carcinogenesis pathway at which these compounds exert their actions. 16 Thus, chemoprevention has the potential to become a major component of CRC control.…”
Section: Introductionmentioning
confidence: 99%
“…Lynch syndrome is a hereditary autosomal dominant disorder characterized by considerably increased risks of colonic and extracolonic tumors and earlier age of onset. It was associated with mutations in the MMR genes (3,4). Of the 3000 germline sequence variants reported in the International Society for Gastrointestinal Hereditary Tumors database, the MLH1 and MSH2 genes were the most prevalent with rates at 40% and 34%, respectively, followed by 18% for MSH6 and 8% for PMS2.…”
Section: Discussionmentioning
confidence: 99%
“…Lynch syndrome (LS) is an autosomal dominant disorder characterized by an increased risk of the early development of colorectal cancers and other extracolonic carcinomas (1,2). Mutations affecting the DNA mismatch repair (MMR) genes (MLH1, MSH2, MSH6, and PMS2) were found to cause this condition (3,4). Indeed, approximately 90% of the alterations are attributable to the MLH1 and MSH2 genes and are spread over all regions without hotspots (5).…”
Section: Introductionmentioning
confidence: 99%